GUIDING PRINCIPLES OF CREATING AGRO-FOOD SYSTEMS RESISTANT TO SHOCKS AND CRISES - POHORIELOVA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2024)
With the development and transformation of society, the environment, vulnerability factors and associated risks, as well as the range of stresses and shocks that have to be faced, also change. Understanding these processes is essential for developing effective interventions to manage multiple risks and increase the resilience of agri-food systems by strengthening their capacity to avoid, anticipate, manage, adapt and transform risks. Therefore, the formation of agro-food systems resistant to shocks and crises should become one of the key strategic goals of ensuring the national food security of the state. Ensuring the sustainability of agro-food systems involves increasing their ability to prevent risks associated with specific shocks and stresses, anticipate and overcome them, adapt to them and transform. In addition, it involves guaranteeing the fulfillment of their special functional purpose, which is to support the functioning of the livelihoods of participants in agro-food systems and ensure food security and nutrition for all. As a result of the research: 1) a conceptual scheme for analyzing the stability of agro-food systems in Ukraine as a result of shocks and crises caused by the war was developed. The analysis is based on three fundamental questions: 1) "resistance to what?" - an object of stability, "sustainability of what?" – the subject of sustainability and 3) "sustainability for what?" - the goal of stability; 2) it has been proven that in order to increase the resilience of agri-food systems, it is important that policies, strategies and programs are guided by three main principles: 1) preparedness for failures, 2) implementation of a system-wide, multilateral and cross-sectoral approach taking into account multiple risks and 3) consideration of various issues and components politicians The guiding principles in combination with the basic principles form the key factors influencing the components of the national agro-food system, which ensure their sustainability.